ANALISIS CITY BRANDING DALAM PENGEMBANGAN DESTINASI PARIWISATA KABUPATEN JAYAPURA - Bawanti, Ari (Sekolah Tinggi Pariwisata AMPTA, 2016)
Jayapura district is a district located in the province of Papua. Unidirectional on the vision and mission of